Treatment Satisfaction Among Patients with Moderate-to-severe Psoriasis - Finch, Tracey (J Clin Aesthet Dermatol, 2015)
Objective: Various treatment options are available for the management of psoriasis; however, there remains a scarcity of literature regarding satisfaction levels among these patients. Given that treatment dissatisfaction is associated with lower levels of adherence, the objective of the present study was to establish satisfaction levels among patients with psoriasis. Design: A modified version of a previously validated satisfaction questionnaire was completed by patients. Setting: Dermatology outpatient department (Solihull, United Kingdom). Participants: Thirty-eight patients with psoriasis (median age 43). Measurements: The questionnaire addressed various domains of satisfaction including satisfaction with safety, convenience, information provision, and finally global satisfaction with 1) topical treatments, 2) phototherapy, and 3) systemic treatments. Results: Mean global satisfaction with phototherapy and systemic treatments was significantly higher than with topical treatments. The authors’ findings also showed that 20 percent of patients receiving topical treatment were dissatisfied with the convenience of the treatment. Interestingly, the only domain causing dissatisfaction among patients receiving systemic therapies (largely biologies) was safety. Despite this, satisfaction with both systemic treatment and phototherapy was higher than has been previously reported. Conclusion: The findings of this study indicate that levels of satisfaction with phototherapy and systemic treatments are high, which is encouraging for both clinicians and patients. However, there are undoubtedly higher levels of dissatisfaction with topical treatments. Given that topical treatments have the greatest safety profile, they will continue to be the first-line treatment for psoriasis. Advances that focus on patient concerns should become a priority in order to improve compliance and reduce the need for more costly intervention.